Family nurture in the social skills development of children with intellectual disabilities through daily activities - Mumpuniarti Mumpuniarti; Gena Diniarti; Wening Prabawati; Suparno Suparno (LPMPP Universitas Negeri Yogyakarta, 2021)
In the time of the COVID-19 pandemic, social restriction inhibits social skills. This research examines family nurturing in facilitating social skills development, parents' inclination in facilitating nurturing, and different intensities in nurturing the social skills development of children with intellectual disabilities (ID). This research subject included eight parents of 5–7-year-old children with mild ID who were pursuing preschool special education. It employed a qualitative approach. Data collection was performed through interviews guided with a close-ended questionnaire on 11 social skills categories. Reasons for the development of each social skills category were to be revealed through an open-ended questionnaire. Data analysis involved the categorization of social skills in relation to daily living activities in the family. It was found that the social skills that might be developed through daily living activities in the family were the social skills performed through activities with family. Parents' ability to stimulate the social skills of children with ID tended to be concrete in nature and dependent on other people as models and the intensity on the presence of others to support as media.